Effects of the multiple O-glycosylation states on antibody recognition of the immunodominant motif in MUC1 extracellular tandem repeats12. Issue 6 (14th April 2016) - Rangappa, Shobith; Artigas, Gerard; Miyoshi, Risho; Yokoi, Yasuhiro; Hayakawa, Shun; Garcia-Martin, Fayna; Hinou, Hiroshi; Nishimura, Shin-Ichiro
Abstract : The conformational impact of the clustered O -glycans strongly influences recognition by antibodies of the cancer-relevant epitope in the MUC1 extracellular tandem repeat domain. Abstract : Antibodies that react with human epithelial cell membrane MUC1 glycoprotein with aberrant glycoforms are promising diagnostic and therapeutic reagents in various cancers and interstitial lung diseases. However, the precise epitopes for anti-MUC1 antibodies have remained unclear. Although the MUC1 extracellular domain has multiple O -glycosylation sites within the tandem repeats, there have been few systematic approaches to determine the effects of the multiple O -glycosylation states, in the context of the disease-relevant epitope regions, on antibody recognition. In this study, we established a comprehensive approach for the characterization of anti-MUC1 antibodies by combining microarray-based epitope profiling and NMR-based conformational analysis of synthetic MUC1 glycopeptides. Epitope mapping analysis using a microarray that displayed 23 synthetic MUC1 glycopeptides revealed that anti-KL6/MUC1 monoclonal antibody (anti-KL6 mAb) has absolute binding specificity with an essential epitope, Pro-Asp-Thr[Neu5Acα(2→3)Galβ(1→3)GalNAcα1→]-Arg-Pro-Ala-Pro, in an ultimately glycoform-specific manner when compared with the other well-studied anti-MUC1 mAbs DF3 and SM3, which are directed against the same Pro-Asp-Thr-Arg (PDTR) motif in the tandem repeats. Multiple O -glycosylations at the neighbouring Ser/Thr residues did not disturb this specific recognition by anti-KL6 mAb, even when modified by sterically hindered core 2-type pentasaccharide moieties (SC2). To our surprise, both DF3 and SM3 exhibited a drastic decrease in binding ability with putative MUC1 fragments with an immunodominant PDTR motif when other glycosylation sites were occupied by Tn antigen (GalNAcα1→) or T antigen [Galβ(1→3)GalNAcα1→]. However, modification at the two adjacent Ser residues by O -glycans that contained ST antigen [Neu5Acα(2→3)Galβ(1→3)GalNAcα1→] resulted, exceptionally, in a substantial enhancement of the affinity of DF3 for the PDTR region. These results demonstrated for the first time that the O -glycosylation states around the immunodominant PDTR motif strongly influence the binding potency and profile of DF3 and SM3. NMR studies of the synthetic MUC1 fragments discovered the molecular mechanisms by which multiple O -glycosylations at the adjacent Ser/Thr residues induce significant conformational alterations in the PDTR motif in a glycoform-dependent manner. Anti-KL6 mAb was proved to be the only anti-MUC1 mAb that can recognise a unique glycopeptidic neo-epitope generated via site-specific posttranslational modification by ST antigen independently from O -glycosylation states at the adjacent Ser/Thr residues within the MUC1 tandem repeats.